The Cretaceous succession of northeast Baffin Bay: Stratigraphy, sedimentology and petroleum potential. (November 2021) - Nøhr-Hansen, Henrik; Pedersen, Gunver Krarup; Knutz, Paul C.; Bojesen-Koefoed, Jørgen A.; Śliwińska, Kasia Kamila; Hovikoski, Jussi; Ineson, Jon R.; Kristensen, Lars; Therkelsen, Jens
Abstract: Eleven cored boreholes, with depths up to c. 360 m were drilled in north-east Baffin Bay, a frontier area offshore West Greenland by the vessel Joides Resolution . The cores were part of the Baffin Bay scientific shallow coring program, expedition 344S in 2012, funded by a consortium of eight petroleum companies. The main drilling target was a succession of dipping strata in the Kap York Basin that proved to be of Cretaceous age. Here we report the results of comprehensive core analyses involving lithofacies interpretation, palynological dating, palynofacies studies, isotope geochronology, organic geochemistry and reservoir characterization. The Lower Cretaceous succession comprises sandstones, mudstones and few thin coal beds of Albian age. Terrestrial material and a sparse and low diversity assemblage of brackish-water dinoflagellate cysts (dinocyst) species dominate the organic particles. The sedimentary environments range from floodplain to deep bay and suggest deposition in a large non-marine to brackish embayment. The kerogen type is immature to marginally mature, type III/IV, with very restricted potential for generation of petroleum or gaseous petroleum. The Upper Cretaceous sedimentary succession of Cenomanian–Turonian age consists of black marine mudstone with varying amounts of discrete sand layers. The amorphous organic material and marine dinocysts suggest that most of the succession was deposited in an anoxic–dysoxic to oxygen restricted palaeoenvironment, probably ranging from outer shelf and prodelta fringe to lower delta front. The organic richness and petroleum potential are variable. The black mudstones include organic rich intervals with TOC of 3–6%, HI of 200–350 and SPI value of 3.0, comparable to well-known petroleum source rock successions of this age worldwide. The δ 13 Corg curves for the Cenomanian–Turonian sections display values and trends characteristic of Oceanic Anoxic Event 2 (OAE2). A marine transgression between the Lower and Upper Cretaceous successions caused dramatic changes in depositional environments. Highlights: Eleven shallow cores from Baffin Bay, Greenland dated Albian–Turonian (Cretaceous) . Studies of lithofacies, palynology, palynofacies, isotopes, geochemistry, porosity . Net sandstone thickness of 100 m with an average porosity of 25% . TOC 3–6%, HI 200–350, SPI 3.0 values of organic-rich intervals indicate source rock. δ 13 Corg curves for the Cenomanian–Turonian corresponds to the Oceanic Anoxic Event 2.